2016
DOI: 10.1080/09513590.2016.1223286
|View full text |Cite
|
Sign up to set email alerts
|

Novel adipokines WISP1 and betatrophin in PCOS: relationship to AMH levels, atherogenic and metabolic profile

Abstract: WISP1 and betatrophin may play a key role on the pathogenesis of PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Importantly, with the increase in circulating betatrophin concentration, adipose IR also increased significantly. ese results are consistent with most previous studies, which reported increased serum betatrophin levels in IR individuals or women with PCOS [31][32][33][34]. In a previous study, Adamska et al reported that betatrophin was closely related to IR and islet β-cell secretion.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, with the increase in circulating betatrophin concentration, adipose IR also increased significantly. ese results are consistent with most previous studies, which reported increased serum betatrophin levels in IR individuals or women with PCOS [31][32][33][34]. In a previous study, Adamska et al reported that betatrophin was closely related to IR and islet β-cell secretion.…”
Section: Discussionsupporting
confidence: 92%
“…A novel circulating hormone, betatrophin, secreted both by the adipose tissue and liver, has been found to be elevated in PCOS and strongly associated with androgens, BMI and IR (105). Moreover, betatrophin was shown to be an independent predictor of fibrosis in patients with NAFLD (106).…”
Section: Molecular Basis Including Endocrine Disruptorsmentioning
confidence: 98%
“…Of these studies included, 12 studies recruited patients with T2DM [8, 9, 12-14, 20, 22-27], of which one recruited patients undergoing CD [13], and 5 enrolled GDM [15,16,[28][29][30], 3 enrolled PCOS [17,21,31], 2 enrolled adult with different body weight (BW) [10,32], one enrolled Mets [18] and 2 enrolled NAFLD [19,33]. Twenty-two studies in all included studies were cross-sectional studies, 3 were case control studies.…”
Section: Description Of Included Studiesmentioning
confidence: 99%